2003
DOI: 10.1002/ptr.1404
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐obesity action of Salix matsudana leaves (Part 1). Anti‐obesity action by polyphenols of Salix matsudana in high fat‐diet treated rodent animals

Abstract: In preliminary experiments, polyphenol fractions prepared from the leaves of Salix matsudana reduced the elevation of the rat plasma triacylglycerol level at 3 and 4 h after oral administration of a lipid emulsion containing corn oil, at a dose of 570 mg/kg. The present study examined the anti-obesity action of polyphenol fractions of S. matsudana leaves by testing whether the polyphenol fractions prevented the obesity induced by feeding a high-fat diet to female mice for 9 weeks. Body weights at 2-9 weeks and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 12 publications
1
68
0
Order By: Relevance
“…210 To date no human studies have been carried out. 211,212 These studies showed that oral administration of polyphenol fractions to DIO mice reduced adiposity and body weight. In vitro analysis revealed that S. matsudana extract inhibited the enzyme α-amylase.…”
Section: Salacia Reticulatamentioning
confidence: 99%
See 1 more Smart Citation
“…210 To date no human studies have been carried out. 211,212 These studies showed that oral administration of polyphenol fractions to DIO mice reduced adiposity and body weight. In vitro analysis revealed that S. matsudana extract inhibited the enzyme α-amylase.…”
Section: Salacia Reticulatamentioning
confidence: 99%
“…The effects of S. matsudana are mainly due to the inhibition of carbohydrate and lipid absorption, and the acceleration of fat mobilization through enhancement of NA-induced lipolysis in adipocytes. 211 Although S. matsudana extracts have been shown to have anti-obesity actions in vitro and in rodents, research in humans, especially on the long term effects, is lacking.…”
Section: Salacia Reticulatamentioning
confidence: 99%
“…Moreover, Salix species also have anti-oxidant (Alam et al, 2006), anti-inflammatory (Li et al, 2008), antiobesity (Han et al, 2003), and anti-tumor (Sultana et al, 2004) effects. Salix Koreensis Andersson in DC.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism underlying the reported therapeutic activity may involve, at least, an improvement of insulin sensitivity which can lead to an increase in peripheral glucose utilization [16][17][18] . Scientific records reveal that plants such Panax ginseng [19,20] , Acanthopanax senticosus [21] , Salix matsudana [22] have been reported to posses insulin sensitizing activities in nutrition induced obese animals. A similar mechanism may operate in the plant extracts-treated HFD mice to improve glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%